2021
DOI: 10.1055/s-0040-1713772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small Intestinal Submucosal Graft and Autologous Tissue in Prevention of CSF leak after Posterior Fossa Craniotomy

Abstract: Objective To compare the use of porcine small intestinal submucosal grafts (SISG) and standard autologous material (fascia) in prevention of cerebrospinal fluid (CSF) leak and pseudomeningocele formation after translabyrinthine resection. Setting Set at the tertiary skull base center. Methods This is a retrospective chart review. After Institutional Review Board approval, we performed a retrospective cohort study evaluating CSF leak in patients who underwent resection of lateral skull base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 33 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…The ideal artificial skin coverage should be easy to obtain, convenient to use, bioactive, and protective. Since SIS patch has been used more than 3 decades in the field of medicine, it has been shown to help tissue regeneration and angiogenesis, such as in skull base reconstruction [ 22 , 23 ], upper airway tissue remodeling [ 24 ], tympanic membrane repair [ 25 ], cardiovascular diseases [ 26 ]. The natural three-dimensional ECM framework composed of collagen I, III, and IV and a variety of bioactive substances it contains makes it helpful during wound healing [ 7 , 8 ], and this kind of particular composition enables it rapid the rate of angiogenesis and does not activate immune system [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal artificial skin coverage should be easy to obtain, convenient to use, bioactive, and protective. Since SIS patch has been used more than 3 decades in the field of medicine, it has been shown to help tissue regeneration and angiogenesis, such as in skull base reconstruction [ 22 , 23 ], upper airway tissue remodeling [ 24 ], tympanic membrane repair [ 25 ], cardiovascular diseases [ 26 ]. The natural three-dimensional ECM framework composed of collagen I, III, and IV and a variety of bioactive substances it contains makes it helpful during wound healing [ 7 , 8 ], and this kind of particular composition enables it rapid the rate of angiogenesis and does not activate immune system [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…F Appearance of the affected hand during the last time follow-up, and texture mismatch and scar hyperplasia could be observed. The result of the SCAR scale was 8 and the sensation of the newborn skin was S3 according to the BMRC grading system Zang et al Journal of Orthopaedic Surgery and Research (2023) 18:50 in the field of medicine, it has been shown to help tissue regeneration and angiogenesis, such as in skull base reconstruction [22,23], upper airway tissue remodeling [24], tympanic membrane repair [25], cardiovascular diseases [26]. The natural three-dimensional ECM framework composed of collagen I, III, and IV and a variety of bioactive substances it contains makes it helpful during wound healing [7,8], and this kind of particular composition enables it rapid the rate of angiogenesis and does not activate immune system [9,10].…”
Section: Fig 2 Representative Images Of Two Cases In Group a (A-c) An...mentioning
confidence: 99%
“…Several studies reported an onlay technique to seal the dura, employing autologous grafts, xenografts and synthetic dural substitutes. 17,21,22,25,42,[47][48][49][50] Autologous onlays consisted of fascia grafts, harvested either from the abdomen or thigh. 17,22,25,42,48,51 Variations in the autologous onlay technique centred around the size of the graft used, ranging from slightly larger than the dural defect to a 'peri cranial graft basket' 47 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…17,21,22,25,42,[47][48][49][50] Autologous onlays consisted of fascia grafts, harvested either from the abdomen or thigh. 17,22,25,42,48,51 Variations in the autologous onlay technique centred around the size of the graft used, ranging from slightly larger than the dural defect to a 'peri cranial graft basket' 47 . Advantages of autologous grafts include their cost profile, universal availability, and high compatibility with the local tissue environment, while drawbacks include donor site-related complications and increased operative times.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation